Efektivitas BYOND By BSI dalam Kualitas Pelayanan dan Kepuasan Nasabah di BSI KCP Krian Sidoarjo - Eva Fa’izatul A’yun; Mariyah Ulfah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effectiveness of BYOND by BSI in improving service quality and customer satisfaction at BSI KCP Krian Sidoarjo. BYOND by BSI is a digital banking platform designed to improve service quality with various superior features, such as financial transactions, account opening, and service consultations based on sharia principles. The research method used is a qualitative approach with descriptive method. Data was obtained through interviews and Focus Group Discussions (FGD) with employees from various divisions. The results showed that BYOND by BSI provides significant convenience in banking transactions, reduces queues at tellers, and offers sharia-based features that increase customer loyalty. However, challenges such as low digital literacy and transaction security concerns still need to be addressed. The implementation of BYOND by BSI has been positive in improving service quality and customer satisfaction, and strengthening BSI's image as an innovative Islamic bank. BSI needs to continue to improve digital education, strengthen security systems, and develop new features to make BYOND by BSI more effective in the future.